Analysis of Eastern Indonesia's Electricity Demand 2014-2019 - Fatmawati, Anisa (Journal of Economic Education, 2021)
Electricity is a primary need for all people. Electricity is an essential factor in the development of every country, both in terms of economic and social aspects. This study aims to analyze the effect of connected power capacity, electricity prices, population, GRDP on electricity demand in Eastern Indonesia. The method used in this research is panel data regression analysis. This study indicates that the variables connected to power capacity and per capita GRDP have a positive and significant effect on electricity demand in the Eastern Indonesia region. Meanwhile, the price of electricity has a negative effect on the demand for electricity in Eastern Indonesia areas. Then the population variable has a negative and significant effect on electricity demand Eastern Indonesia areas